Imanência e transcendência: uma leitura comparativa de Nietzsche e do budismo - Alves, Derley Menezes (2019)
The aim of this work is to make an historical and comparative analysis between Nietzsche’s philosophy and Buddhism. We want to demonstrate with such a comparison that the historical contexto in which Nietzsche had learn about Buddhism is fundamental in order to understand how he understood that religion and, at the same time, we want to demonstrate that, when comparing both worldviews emerges with much more force the diferences than de similarities between them, especially if we take the key words that we understand describes each of those worldviews, that is to say, immanence and transcendence. The philosophy of Nietzsche consists of a radical defense of immanence in opposition with all kind of metaphysics, Buddhism, on the other hand, is a religion with ot’s own modes of thinking and achieving transcendence that have in the concept of Nibbana or Nirvana it’s highest point